An Investigation on The Impact of Orally Administered Celery and Orange Juices on The Production of Collagen in Rats Exposed to Ultraviolet-B Light - Arhani, Adli; Fioni, Fioni; Pratama , Irza Haicha (Sean Institute, 2023)
At the correct dosage, ultraviolet (UV) radiation has many positive health effects and is essential for the body. The flip side is that exposure to excessive amounts of ultraviolet light (UV) can be harmful. Repetitive exposure to UVB light causes reactive oxygen species (ROS) to be produced, reducing the production of antioxidant enzymes, increasing oxidative protein modification, and causing glycation and lipid peroxidation products to accumulate. Because of this, it's essential to take precautions to guard the skin from free radical damage and slow the aging process by employing antioxidants in various forms. In this study, rats were exposed to UVB light and then given either celery juice (Apium graveolens) or orange juice (Citrus) orally to see if it would increase the quantity of collagen in the rats. True experimentation, or study in a controlled laboratory setting, is the method of choice. Each of the three groups consisted of eight white rats, for a total of twenty-four rats. Due to their high concentrations of antioxidant components, the phytochemicals found in celery and orange juices were determined to have therapeutic potential in the study's conclusions. With a collagen density value of 3+ and a density of collagen fibers in the skin ranging from 50 to 90% per field of view, the group given orange juice had a more substantial impact on the collagen growth of rat skin tissue after exposure to UVB light compared to the group given celery juice.